Discussion of Public Health Education and Training, and the Needs of the Future Public Health Workforce - Gary Nelson (Georgia Southern University, 2017)
Georgia enjoys a wealth of public health capacity ranging from governmental public health to academic programs as well as local, state, and internationally acclaimed organizations. Leadership is evident across public health policy, practice and research. In the closing plenary of the 2017 Annual Meeting-Faces of Public Health, GPHA engages leaders in our field in a spirited conversation on the public health workforce. The esteemed panel representing state, national, and international public health organizations will reflect on the needs of a 21st Century workforce: prepared to respond beyond emergencies and identified threats; able to adapt to an increasing complex technological, political and economic environment; committed to affecting the economic and social determinants of health inequities; and collaborating to advance the knowledge base aligned with core public health functions and essential services. Are professional standards, qualifications and credentials appropriately calibrated for the needs and opportunities ahead? How has the underlying science base for public health practice, leadership and research changed? As stewards of population health, is the workforce equipped to provide thought leadership on health policy and legislation? What's working and what's not working in the recruitment, preparation, and retention of Georgia's large and diverse public health workforce? The audience will be invited to join the panel in this engaging dialogue.